Peranan Teori Belajar Humanistik dalam Keberhasilan Belajar di Abad 21 - Tasyirifiah, Tahniah; YS, Arba’iyah; Wibisono, Zaidan Muzakki (ANWARUL, 2023)
This paper examines humanistic theory which is often referred to as learning theory which is oriented towards aspects of humanizing humans so that they can reach their maximum potential level. This article was created with the intention to discuss the role of humanistic learning theory on the success of learning in the present. The chapters in this paper are also made to the maximum extent possible to answer how the role of humanistic learning theory is to the success of learning primarily in the 21st century. The humanistic principles used are based on the opinion of Carl Rogers. This article also identifies challenges and obstacles in implementing humanistic learning theory such as a curriculum that focuses on academic goals, time constraints, and pressure for fast results to be some of the challenges faced by educators. There are also five strategies for applying humanistic learning theory.